Teacher Professionalism From the Perspective of the Sociology of Islamic Education in the Era of Revolution 5.0 - Faidil Fathurrohman; Tutuk Ningsih; M. Slamet Yahya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study examines teacher professionalism from the perspective of the sociology of Islamic education in the context of the Revolution 5.0 era. This study uses a qualitative approach through a literature review method by examining various theories, research results, and policy documents relevant to the development of the teaching profession and the integration of technology with Islamic values. The results of the study indicate that teacher professionalism is not sufficient based on technical competence alone, but must be accompanied by digital literacy, ethical awareness, and spiritual depth derived from the principles of the Koran. In Islamic education, teachers not only serve as mu'allim (teacher), but also murabbi (moral educator) and murshid (spiritual guide). Therefore, professional teachers in the Revolution 5.0 era are required to be able to combine intellectual skills, spiritual integrity, and social sensitivity. This study emphasizes that strengthening teacher professionalism needs to be done through an integrative approach that unites the dimensions of humanity and technology within the framework of Islamic spirituality. The concept of ulul albab—which reflects the ability to think critically, remember God, and do good—is a relevant conceptual model in building teacher professionalism with Islamic character amidst the changes of the digital era.